Harmony of Law and Religion: A Maqāṣid Ash-Sharī'ah Analysis of Marriage Registration According to the Fiqh and Law No. 1/1974 - sehabudin (QURU’: Journal of Family Law and Culture, 2024)
In an effort to regulate marriage and reduce the practice of underhand marriage (sirri) in Indonesia, the government has imposed two requirements: material and administrative requirements. Material requirements include provisions related to the pillars of marriage, both those stipulated in fiqh and the law. Meanwhile, the administrative requirements relate to marriage registration, which is regulated in Article 2 paragraph (2) of Law No. 1/1974 on Marriage. The procedure for this recording is explained in Government Regulation Number 9 of 1975. The addition of marriage registration as a condition of marriage has caused controversy among Indonesian legal experts. This controversy is caused by the interpretation of Article 2 paragraphs (1) and (2) of the Marriage Law, as well as differences in the concept of walīmah and Surah Al-Baqarah (2): 282, as well as the necessity of recording in the field of muamalah. This research is a literature research that uses literature study as the main source of data. This data collection method includes primary, secondary, and tertiary data, with a descriptive-analytical and comparative approach. The analysis involves the concept of marriage registration in the Book of Jurisprudence and Law No.1/1974 as well as the urgency for the perpetrators of underhand marriage using maqāṣid ash-sharī'ah analysis. The results show that marriage registration in the Book of Jurisprudence and Law No.1/1974, by applying maqāṣid ash-sharī'ah analysis, shows that the command to register marriage is implicit in the Book of Jurisprudence and explicit in the UUP. Marriage registration, especially for perpetrators of irregular marriages, is in accordance with the objectives of syarak. A marriage certificate can protect religion, soul, mind, offspring, and property before the law, ensuring the benefit of the household (harmonious and lasting family) is achieved.